Effect of different core materials in very low voltage induction motors for electric vehicle - Fransisco Danang Wijaya; Iftitah Imawati; Muhammad Yasirroni; Adha Imam Cahyadi (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2021)
The use of squirrel cage induction motor for electric vehicle (EV) has been increasingly popular than permanent magnet and brushless motors due to their independence on rare materials. However, its performance is significantly affected by the core materials. In this research, induction motors performance with various core materials (M19_24G, Arnon7, and nickel steel carpenter) are studied in very low voltage. Three phases, 50 Hz, 5 HP, 48 V induction motor were used as the propulsion force testbed applied for a golf cart EV. The aims are to identify loss distribution according to core materials and compare power density and cost. The design process firstly determines the motor specifications, then calculates the dimensions, windings, stator, and rotor slots using MATLAB. The parameters obtained are used as inputs to ANSYS Maxwell to calculate induction motor performance. Finally, the design simulations are carried out on RMxprt and 2D transient software to determine the loss characteristics of core materials. It is found that the stator winding dominates the loss distribution. Winding losses have accounted for 52-55 % of the total loss, followed by rotor winding losses around 25-27 % and losses in the core around 1-7 %. Based on the three materials tested, nickel steel carpenter and M19_24G attain the highest efficiency with 83.27 % and 83.10 %, respectively, while M19_24G and Arnon7 possess the highest power density with 0.37 kW/kg and 0.38 kW/kg whereas, in term of production cost, the Arnon7 is the lowest.